Visiting Family in Huntington Beach - Watkins, Howard::::::::: (1983)
Rose Watkins, Wanda St. James, Adam Watkins, Christine Watkins, Howard Watkins, Albert Watkins Celebrating Albert's 65th birthday at The Seafood Broiler in Seal Beach, CA